Analysis of the factors that increase employee performance at PT BPR Tata Anjung Sari - I Gede Putu Kawiana (Jurnal Info Sains : Informatika dan Sains, 2023)
The significance of employee performance is vital in attaining organizational objectives and sustaining a competitive edge within a progressively intricate marketplace. Hence, the primary objective of this study is to investigate the determinants that have a favorable impact on enhancing employee performance within the context of PT BPR Tata Anjung Sari. The research scope include the examination of work discipline, work environment, remuneration, and work aptitude as pertinent variables. The present study used a descriptive and correlational methodology. The employed sampling technique was purposive sampling, encompassing a comprehensive sample size of 103 individuals who were employees. The data was obtained by administering a questionnaire that had undergone rigorous testing to ensure its validity and reliability. The coefficient of determination was utilized for data analysis using SPSS version 26 software. The findings indicate that there is a positive correlation between work discipline characteristics and employee performance, as well as work environment and salary variables. Nevertheless, it is worth noting that the variable of job ability does not exhibit a statistically significant impact on employee performance. In summary, the findings of this study suggest that the combined influence of work discipline, work environment, salary, and work ability significantly affects employee performance.